(untitled) - Dunne, Lavon J. (New York, 2002)
Take a bite out of a bestseller!Trusted by health-conscious people for over 30 years, McGraw-Hill's NUTRITION ALMANAC--the oldest healthy eating and supplementation guide around--supplies accurate, up-to-date, and impartial information.That's why over 2.5 million copies have been sold!The new Fifth Edition contains the latest material on the nutrition/disease front: solid information on the latest supplementation, herbs, and vitamins; additional exercise/nutrition benefits and interactions; and much more.*Examines the connections between nutrition and disease*Clarifies the role of proteins, carbohydrates, fats, vitamins, and minerals*Details the optimal supplementation dosages for individual needs*Presents the latest scientific data on health and eatingINVALUABLE TO: *Physicians *Nurses *Dieticians*Scientists*Researchers*Physical Therapists*Physician's Assistants*Chiropractors*Sports Trainers*And individuals who want reliable, complete, sensible information on the food they eat, the supplements they take, and the effect these have on their bodies.
Keywords: Nutrition,Health,Food; Composition,Tables